Adapting HIV patient and program monitoring tools for chronic non-communicable diseases in Ethiopia. Issue 1 (December 2016) - Letebo, Mekitew; Shiferaw, Fassil
Abstract Background Chronic non-communicable diseases (NCDs) have become a huge public health concern in developing countries. Many resource-poor countries facing this growing epidemic, however, lack systems for an organized and comprehensive response to NCDs. Lack of NCD national policy, strategies, treatment guidelines and surveillance and monitoring systems are features of health systems in many developing countries. Successfully responding to the problem requires a number of actions by the countries, including developing context-appropriate chronic care models and programs and standardization of patient and program monitoring tools. Methods In this cross-sectional qualitative study we assessed existing monitoring and evaluation (M&E) tools used for NCD services in Ethiopia. Since HIV care and treatment program is the only large-scale chronic care program in the country, we explored the M&E tools being used in the program and analyzed how these tools might be adapted to support NCD services in the country. Document review and in-depth interviews were the main data collection methods used. The interviews were held with health workers and staff involved in data management purposively selected from four health facilities with high HIV and NCD patient load. Thematic analysis was employed to make sense of the data. Results Our findings indicate the apparent lack of information systems for NCD services, including the absence of standardized patient and program monitoring tools to support the services. We identified several HIV care and treatment patient and program monitoring tools currently being used to facilitate intake process, enrolment, follow up, cohort monitoring, appointment keeping, analysis and reporting. Analysis of how each tool being used for HIV patient and program monitoring can be adapted for supporting NCD services is presented. Conclusion Given the similarity between HIV care and treatment and NCD services and the huge investment already made to implement standardized tools for HIV care and treatment program, adaptation and use of HIV patient and program monitoring tools for NCD services can improve NCD response in Ethiopia through structuring services, standardizing patient care and treatment, supporting evidence-based planning and providing information on effectiveness of interventions.